1981
DOI: 10.1111/j.1751-1097.1981.tb05338.x
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Comparison of Chlorophyll Bilayers Formed With and Without Solvent

Abstract: Bimolecular lipid membranes are formed from solutions containing lecithin and chlorophyll‐a (chl‐a) in various molar ratios. Both the Mueller‐Ruding technique as well as the solvent free, Montal‐Mueller technique are used to form bilayers. In both methods, increasing the chl concentration produces greater photosensitivity. The photocurrent/area is about an order of magnitude higher in bilayers formed with the solvent free method, under similar conditions. From the quantum yield calculations, it appears that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…We found that the photocurrent/area was about an order of magnitude higher in bilayers formed with the solvent-free method. From quantum yield calculations, it appeared that the higher photocurrent/area obtained with the Montal-Mueller membranes could not be explained solely due to the greater concentration of pigment molecules in the solvent-free system, thus suggesting a possible role of chlorophyll-chlorophyll interactions (Rich and Brody 1981). We went on to study the effects that various carotenoids played on increasing electron transfer in the solvent-free bilayers and discovered that the dihydroxy carotenoids were significantly more efficient in electron transfer than beta carotene (Rich and Brody 1982).…”
Section: Mrmentioning
confidence: 95%
“…We found that the photocurrent/area was about an order of magnitude higher in bilayers formed with the solvent-free method. From quantum yield calculations, it appeared that the higher photocurrent/area obtained with the Montal-Mueller membranes could not be explained solely due to the greater concentration of pigment molecules in the solvent-free system, thus suggesting a possible role of chlorophyll-chlorophyll interactions (Rich and Brody 1981). We went on to study the effects that various carotenoids played on increasing electron transfer in the solvent-free bilayers and discovered that the dihydroxy carotenoids were significantly more efficient in electron transfer than beta carotene (Rich and Brody 1982).…”
Section: Mrmentioning
confidence: 95%